Using Online Reviews to Drive Person-Centered Care: An HCAHPS-Validated Approach - Joseph G Taylor PhD; Meghan P Leaver PhD; Alex Griffiths PhD (Journal of Patient Experience)
Person-centered care focuses on the needs of the individual receiving care, and involves cooperation between patients and health professionals to develop and monitor care. This research demonstrates that online patient reviews provide a rich, real-time, and detailed source of patient experience that can be used for this purpose. This study also shows that unstructured online data can be quantified using machine learning and natural language processing to automatically flag and rate patient reviews. We describe a supervised learning approach, training a model on a large dataset of manually annotated patient reviews. We report model scores of 99% accuracy in predicting overall score, and 93% to 99% in predicting relevance to seven domains of patient experience, such as Effective Treatment, Fast Access, and Emotional Support. Furthermore, we show statistically significant alignment between these aggregated online patient reviews and HCAHPS star ratings—a “gold-standard” measure of care quality for hospitals in the United States. This approach enables benchmarking between health systems and evaluating the impact of interventions on patient experience, while quantifying and enhancing the patient-centeredness of care.